Obsessions and compulsions in anorexia nervosa subtypes - Katherine A. Halmi; Suzanne R. Sunday; Kelly Klump; Michael Strober; James F. Leckman; Manfred M. Fichter; Allan S. Kaplan; D. Blake Woodside; Janet Treasure; Wade H. Berrettini; Mayadah Al Shabboat; Cynthia M. Bulik; et al. (2003)
Abstract Objective Obsession and compulsions in anorexia nervosa (AN) patients are often confused with the preoccupations and rituals that are characteristic of obsessive‐compulsive disorder (OCD). We examined the type and frequency of characteristic OCD obsessions and compulsions in a large sample of AN patients. Method In personal interviews with 324 AN patients, we assessed lifetime histories of eating disorder symptomatology and obsessive‐compulsive behaviors with valid semistructured interviews. Checklist category sums on the Yale‐Brown Obsessive Compulsive Scale were compared between AN and OCD subjects using generalized estimating equations. Results Lifetime obsessions and compulsions occurred in 68% of the AN restricting type and in 79.1% of the AN binge/purge type. The AN subgroups did not differ from OCD controls inr frequency of obsessions in the symmetry and somatic categories or in the compulsion categories of ordering and hoarding. In all other categories, the AN subgroups had a significantly lower frequency compared with the OCD controls. Discussion Some common phenotype characteristics shared by most AN and OCD patients suggest these disorders may share common brain behavioral pathways. However, the lack of complete overlap indicates they most likely have different loci of pathology within those pathways. © 2003 by Wiley Periodicals, Inc. Int J Eat Disord 33: 308–319, 2003.